2004
DOI: 10.1074/jbc.m401231200
|View full text |Cite
|
Sign up to set email alerts
|

Aggregates Are the Biologically Active Units of Endotoxin

Abstract: For the elucidation of the very early steps of immune cell activation by endotoxins (lipopolysaccharide, LPS) leading to the production and release of proinflammatory cytokines the question concerning the biologically active unit of endotoxins has to be addressed: are monomeric endotoxin molecules able to activate cells or is the active unit represented by larger endotoxin aggregates? This question has been answered controversially in the past. Inspired by the observation that natural isolates of lipid A, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
193
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 215 publications
(211 citation statements)
references
References 26 publications
14
193
0
Order By: Relevance
“…For example, it may be that the differences we observed are due to different degrees of aggregation and/or differing physical states of the micellar aggregates that are formed by the various forms of LPS used in these studies (42)(43)(44). Studies by Mueller et al (45) suggest that aggregates, rather than monomers, are the active units of endotoxin, and that the physical states of these aggregates are a function of their hydrophobicity. In contrast, several other studies have suggested that LPS monomers, rather than LPS aggregates, are important for function (46 -48).…”
Section: Discussionmentioning
confidence: 88%
“…For example, it may be that the differences we observed are due to different degrees of aggregation and/or differing physical states of the micellar aggregates that are formed by the various forms of LPS used in these studies (42)(43)(44). Studies by Mueller et al (45) suggest that aggregates, rather than monomers, are the active units of endotoxin, and that the physical states of these aggregates are a function of their hydrophobicity. In contrast, several other studies have suggested that LPS monomers, rather than LPS aggregates, are important for function (46 -48).…”
Section: Discussionmentioning
confidence: 88%
“…Unfortunately, the exact chemical structure of the lipid A moieties of the two LPS fractions was not be analyzed in detail, it seems only that fraction 4 may be slightly underacylated as compared to complete hexaacyl lipid A. Such change of the acyl chain moiety, however, would not be observable in the bioactivity test, because in this even an only 50 % hexaacylated lipid A with significant presence of pentaand tetraacylated species can nearly not be differentiated from a 100 % hexaacylated form (34). More important, however, is the finding (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Mueller et al demonstrated that the aggregate is an active unit of endotoxin; Endotoxin aggregates induced the secretion of TNF-a from human mononuclear cells, but the monomers did not. 15) Their observations suggest that the formation of aggregates is essential for recognition by endotoxin receptors, including TLR4. Our observations were consistent with theirs in that endotoxin aggregates, such as aq-OL, aq-lipid A, or-OL and or-lipid A, induced the secretion of TNF-a from mouse macrophages; however, the reduced ability of or-OL and or-lipid A to induce the secretion of IL1b from mouse macrophages could not be explained by their observations.…”
Section: Discussionmentioning
confidence: 99%